Abnormal T2 relaxation time in the cerebellar vermis of adults sexually abused in childhood:: potential role of the vermis in stress-enhanced risk for drug abuse - Anderson, Carl M.; Teicher, Martin H.; Polcari, Ann; Renshaw, Perry F. (Psychoneuroendocrinology, 2002)
Recent studies suggest that childhood sexual abuse (CSA) elicits a cascade of neurohumoral events that affect brain development and is also a risk factor for the later development of substance abuse. We hypothesize that the cerebellar vermis may be a key region linking these observations. The vermis has a protracted ontogeny and a high density of glucocorticoid receptors, rendering it highly susceptible to early stress. The vermis modulates dopamine turnover in the accumbens and receives direct dopamine input through fibers with dopamine transporters. To test this hypothesis, steady-state functional magnetic resonance imaging (fMRI) (T2 relaxometry) was performed to assess resting blood flow in the vermis of 24 young adults (18–22 years) selected by screening from a large community sample. Eight subjects had a history of repeated CSA but were unmedicated and not under psychiatric care. Sixteen subjects were age-matched controls who had no personal or family history of Axis I psychiatric disorders. All subjects were screened to exclude known abnormalities affecting brain development, and any history of drug or alcohol abuse. CSA subjects had higher T2 relaxation time (T2-RT) than controls in the vermis but not in cerebral or cerebellar hemispheres. Vermal T2-RT correlated strongly with Limbic System Checklist (LSCL-33) ratings of temporal lobe epilepsy (TLE)-like symptomatology. From 537 prescreened young adults we found that their frequency of substance use was associated with a monotonic increase in LSCL-33 ratings and depression scores. Together these findings suggest that early trauma may interfere with the development of the vermis, and produce neuropsychiatric symptoms associated with drug use.